IMPLEMENTASI NILAI - NILAI KEBANGSAAN YANG BERSUMBER KEPADA PANCASILA DAN UUD 1945 DALAM PENERAPAN PENCEGAHAN CYBER BULLYING DI SOSIAL MEDIA - Ali Akbar Hidayat; Edy Soesanto, Muhammad Ibnu Hilmy (ADISAM PUBLISHER, 2024)
This research aims to analyze cyberbullying which includes definitions, aspects, factors, characteristics, impacts and prevention. Cyberbullying is bullying that is carried out repeatedly on purpose, such as making fun of, or activities that intervene and also degrade the target being bullied on social media, for example Instagram. This act of cyberbullying has a negative impact on victims of bullying, especially teenagers, who dominate the use of social media. According to a 2018 survey in Indonesia, 49% of internet users experienced cyberbullying and only 3.6% reported incidents of cyberbullying. Cyberbullying can be interpreted as a variety of oflenses regulated in general criminal law in Indonesia, namely those contained in the Criminal Code (KUHP). The articles of the Criminal Code that are relevant in regulating cyberbullying oflenses are those listed in Chapter without the right to distribute and/or transmit and/or make accessible electronic information and/or electronic documents which contain defamatory or insulting content. The method used in this research is literature study by comparing theories and previous research then looking at the similarities and diflerences, where in this research the researcher uses relevant theories then the data used in this research is in the form of journals, articles and books. The results of the research that has been carried out provide information on the impacts experienced by victims of cyberbullying, such as depression, anxiety, and withdrawal from social life. Self-control and ways to prevent cyberbullying behavior are: having ethics when using social media, not just talking and being able to make the right decisions, and being able to choose a good environment so that we don't avoid cyberbullying behavior